Indicadores de Alfabetização Científica sobre o tema Evolução Biológica nas coleções de Ciências da Natureza do Ensino Médio aprovadas no PNDL/2021 - Cazarotti, Ana Cláudia (2024)
In this work we investigated the topic of biological evolution based on the theoretical framework of scientific literacy and scientific literacy indicators of scientific literacy, in the natural science collections approved in the PNLD 2021, which correspond to the books offered to (new) secondary education. Scientific literacy as we understand it is a process in which students have the opportunity to understand the nature of science and that science teaching should not be limited to addressing only concepts and theories, but should also be concerned with the way in which this knowledge is constructed and how its consequences interfere in society (HURD, 1998, AULER; DELIZOICOV, 2001, NORRIS; PHILLIPS, 2003, SASSERON; CARVALHO, 2008). This scientific literacy provides the individual with the chance to understand the world from the point of view of science and exercise their role as a citizen. (MOTOKANE, 2015). Within the teaching of different science contents, the teaching of evolution is considered a central and unifying axis for the teaching of biology, (DOBZHANSKY, 1973) even though there are some biological concepts in which evolution does not interfere with their understanding. We find in the textbook the source of scientific information most commonly used in the classroom, becoming the main pedagogical support material for teachers and students, assuming the function of materializing the main knowledge related to an area of knowledge. Biological evolution began to be found in textbooks in the 1930s, presented as an integral part of paleontology and heredity content (ALMEIDA; FALCÃO, 2010). Therefore, we believe the textbook is material of significant importance for analysis so that it can support students and teachers on their journey in the classroom. Our research paradigm is qualitative, according to Minayo and Sanches (1993). Our research method fits into documentary research according to Lüdke and André (2018). We noticed that four of the seven collections analyzed provide moments that allow the eight expanded scientific literacy indicators to occur. In three collections we did not observe any possibility of developing one or two indicators. Even though the textbook is a tool to support the teacher's work, and an element that can enable students to become scientifically literate, its use may end up not being meaningful if it cannot meet the premises of scientific literacy. The expectation of this study is to contribute to academia and the advancement of knowledge that it provides us, and to support the processes that occur in the classroom, privileging the critical and reflective formation of the student, considering their well-being, that of society and the environment.